Unveiling Views: Perspectives of Faculty Holding Doctoral Degrees on Gender Disparities in Academic Professorships - Ganbarova, Narmin (ADA University, 2024)
This is a qualitative study that investigated the fundamental factors contributing to gender imbalance in Azerbaijani academia, focusing on female professors holding Doctor of Science and Doctor of Philosophy degrees. Moreover, the research explored the challenges faced by female professors holding doctoral degrees and gained insights into their unique experiences and perspectives about gender disparity. Despite substantial studies on gender-related themes in Azerbaijan, no prior studies have investigated the viewpoints of Doctor of Philosophy and Doctor of Science holders on gender imbalances in academia. This study explored two research questions: (1) How do highly qualified scientific staff perceive gender disparity in rank and scientific degrees in academia in Azerbaijan? (2) What are the female professors’ holding doctoral degrees experiences and perspectives on addressing gender disparity in academia? To address the mentioned research questions data was collected through semi-structured interviews with 18 professors and holders of doctoral degrees from three public universities. Key themes emerged, including family-related issues, salary concerns, gender stereotypes, and biased views. While research suggests the existence of a global gender wage gap, respondents' experiences differ. The primary concern of the respondents lies in insufficient overall income rather than dissatisfaction with the gender-based wage gap. The findings underline the need of systemic change in addressing biases, promoting gender equality, and creating inclusive settings that support women's academic achievement. Overall, this research advances our understanding of gender dynamics in Azerbaijani academia and informs targeted efforts to improve fairness and inclusiveness.
Keywords: Women professors -- Azerbaijan; Women in academia -- Azerbaijan; Doctor of Philosophy degrees -- Women -- Azerbaijan; Azerbaijan -- Education -- Gender issues; Azerbaijan -- Women in higher education; Education